Role of prostanoids, nitric oxide and endothelin pathways in pulmonary hypertension due to COPD - Alqarni, Abdullah A.; Aldhahir, Abdulelah M.; Alghamdi, Sara A.; Alqahtani, Jaber S.; Siraj, Rayan A.; Alwafi, Hassan; AlGarni, Abdulkareem A.; Majrshi, Mansour S.; Alshehri, Saad M.; Pang, Linhua (Frontiers in Medicine, 2023)
Pulmonary hypertension (PH) due to chronic obstructive pulmonary disease (COPD) is classified as Group 3 PH, with no current proven targeted therapies. Studies suggest that cigarette smoke, the most risk factor for COPD can cause vascular remodelling and eventually PH as a result of dysfunction and proliferation of pulmonary artery smooth muscle cells (PASMCs) and pulmonary artery endothelial cells (PAECs). In addition, hypoxia is a known driver of pulmonary vascular remodelling in COPD, and it is also thought that the presence of hypoxia in patients with COPD may further exaggerate cigarette smoke-induced vascular remodelling; however, the underlying cause is not fully understood.Three main pathways (prostanoids, nitric oxide and endothelin) are currently used as a therapeutic target for the treatment of patients with different groups of PH. However, drugs targeting these three pathways are not approved for patients with COPD-associated PH due to lack of evidence. Thus, this review aims to shed light on the role of impaired prostanoids, nitric oxide and endothelin pathways in cigarette smoke-and hypoxia-induced pulmonary vascular remodelling and also discusses the potential of using these pathways as therapeutic target for patients with PH secondary to COPD.